VALIDATION OF ELDERLY ABUSE ASSESSMENT TOOL - Joel Rey Ugsang Acob (Belitung Nursing Journal, 2020)
Background: Several screening tools for elderly abuse have been developed but they have rarely been validated properly for wider use. The multiplicity of the tools available revealed the need to develop through collaborative research, a simple and reliable tool that can be adapted and used in different geographical and cultural settings. As the cases of abuse increase, nurses are in a position to rescue this vulnerable population through equipping knowledge and be knowledgeable on using elderly assessment tool for abuse cases. Objective: To validate the developed Filipino-based elderly abuse assessment tool. Methods: The study utilized descriptive confirmatory method design and underwent validation and reliability process. Five experts conducted the scrutiny during validation and 220 elderly clients’ subjected the tool for reliability tests. Data are analyzed using SPSS version 23, while frequency and percentage were used for continuous variable. Results: The Elderly Abuse Assessment Tool is valid and reliable. The tool is clear in terms of the word composition, the texts are understood easily, comprehensive, and relevant based on expert reviews. It has I-CVI of 0.84 (44 items) and increases value in its second version to 0.87 (42 items). On one hand, the tool obtained a very high degree of reliability with Cronbach’s Alpha of 0.974 during the second version. Regardless of item numbers are retained, the value remains high. Constructs identified from the validated tool. Kaiser’s criterion or the Eigenvalue result of the second version of the developed tool revealed six factors that can be extracted. However, in the Scree test or plot, only two factors located above the inflection points. This means that two factors or constructs can be named. The researcher decided to choose the lesser number for easier naming of factors. The tool was classified into two constructs, namely physico-sexual and psycho-financial factors, respectively. Conclusion: The Elderly Abuse Assessment Tool (EAAT) is valid and has a very high degree of reliability. Physico-sexual and Psycho-financial are the two major constructs of the tool. Filipino nurses can now articulate their expression of unending caring through the utility of the validated Elderly Abuse Assessment Tool (EAAT).